REPRESENTASI IDENTITAS SEKSUAL TRANSGENDER DALAM FILM THE DANISH GIRL - Syahdan Siregar; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The study is titled sexual identity Transgender Representation in The Film The Danish Girl. The story in the film is taken from a true story that illustrates how one struggled to find appropriate sexual identity with his true identity. This research aims to know the male sexual identity, sexual identity, sexual identity and female transgender in film The Danish Girl. This study uses qualitative methods, with Roland Barthes semiotics analysis approach, taking a focused subject to transgender sexual identity with views through faceted Denoted (signifier) describes the relationship of signifier and signified on reality, meaning explicit. Connotation (signified) describes the relationship of signifier and signified to non-reality, generate an implicit meaning and myth (the myth) explained the habits and beliefs prevailing in the society. In this study the scene is divided into 3 parts are male sexual identity, sexual identity, sexual identity transgender women with 17 scene data analysis unit. The collection of data by specifying the corpus contained in the film in accordance with the categorization of the already determined. The results of this research show that the representation of sexual identity transgender in film The Danish Girl this is. First, look at the sexual identity of men before the women's soul inside of Einar. Second, look at sexual identity more women showing a female figure but still there is the male sexual identity. Third, look at sexual identity transgender featuring female figure where his sexual identity has been forgotten.Keywords : Mass Communication, Semiotics, Transgender